Factors of cyber ethics awareness and its relationship with internet addiction among students from secondary schools in Tambunan - Kristy Elity Sulaiman (2019)
Internet has been the main source of information especially for students because it provides fast information and entertainment for them. The use of Internet among students has been debated especially in terms of addiction, ethical or unethical use of it. Cyberbullying and cybercrime are some of the alarming issues to the society especially to students. This study aims to examine the level of Internet addiction, level of cyber ethic awareness, gender differences according to Internet addiction and cyber ethic awareness, the factors of Internet addiction and its relationship with cyber ethic awareness among students from secondary schools in Tambunan. The modified diagnostic questionnaire for Internet addiction criteria and the four cyber ethic issues: Privacy, Accuracy, Property, Accessibility (PAPA) were used in this study to construct the research conceptual framework. This paper focuses on two main components namely Internet addiction and cyber ethic awareness. A total of 375 respondents were randomly selected from three public schools in Tambunan they were selected regardless of factors such as class, gender, and age. Data was then analysed using IBM Statistical Package for Social Sciences (SPSS) 24 which includes descriptive statistics (mean and standard deviation), t-test, Pearson correlation analysis and multiple regression analysis. Result showed that the level of Internet addiction among students were in mild level with 52.5% (N=197). It was also revealed that the highest percentage is from medium level of cyber ethic awareness with a percentage 49.9% (N=187) followed by high level of cyber ethic awareness at 48.8% (N=183). There were no significant differences in gender according to level of internet addiction but there were significant differences in gender according to cyber ethics awareness among the students. It was found that there was a significant relationship between Internet addiction and cyber ethic awareness among students from secondary school. Finally, Privacy and Property were found to be significant as the factors of Internet addiction. According to these results, it is recommended that schools to include in the curriculum about awareness on Internet addiction and ethical use of the Internet. Parents can contribute to monitor their children when they are surfing the Internet at home.